Pengendalian Persediaan dan Usulan Perencanaan Safety Stock pada Material Biji Plastik SPP-C05 Black Menggunakan Metode Time Series dan Min-Max : (Studi Kasus: PT Bonecom Tricom) - Melly Marcelia Aziza; Susatyo Nugroho Widyo Pramono (STIKes Ibnu Sina Ajibarang, 2025)
Inventory control is a crucial element in supporting the smooth production process in manufacturing companies. PT Bonecom Tricom, a producer of automotive spare parts, faces challenges in managing SPP-C05 Black plastic pellets due to inaccurate estimation methods, resulting in material accumulation in storage. This study aims to propose inventory planning using time series and min-max methods to optimize material requirements. The results show that the Holt-Winter's Multiplicative method provides the best forecasting accuracy with the lowest error rate (MAPE) of 2%. Furthermore, implementing the min-max method can reduce inventory costs by 14.245%. This study is expected to serve as a reference for companies to manage material inventory more effectively and efficiently.